2009
DOI: 10.1103/physrevb.80.045208
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical readout of dark exciton distribution in cuprous oxide

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. An experimental study of the yellow exciton series in Cu 2 O in strong magnetic fields up to 32 T shows the optical activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…The corrections to the binding energy of the n  = 2 level, produced by these mechanisms, are negligible]. Using ε  = 7.5 for the dielectric constant 11,13,28 , we obtain the reduced mass μ  = 0.41 m 0 in agreement with ref. 12 .
Figure 5The magnetoabsorption spectra measured in the Faraday geometry, , together with the theoretically calculated magnetic field dependence of the energies (dashed lines) for the excitons with [panel (a), set 1] S z  = −1 and m  = 0 and [panel (b), set 2] S z  = 0 and m  = −1.
…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The corrections to the binding energy of the n  = 2 level, produced by these mechanisms, are negligible]. Using ε  = 7.5 for the dielectric constant 11,13,28 , we obtain the reduced mass μ  = 0.41 m 0 in agreement with ref. 12 .
Figure 5The magnetoabsorption spectra measured in the Faraday geometry, , together with the theoretically calculated magnetic field dependence of the energies (dashed lines) for the excitons with [panel (a), set 1] S z  = −1 and m  = 0 and [panel (b), set 2] S z  = 0 and m  = −1.
…”
Section: Discussionsupporting
confidence: 86%
“…Due to the exchange interaction between the conduction and valence electrons in the n  = 1 yellow exciton state, the energy of the ortho-exciton is 12 meV higher than that of para-exciton 3,25–28 .…”
Section: Resultsmentioning
confidence: 98%
“…It has been demonstrated that Cu 2 O was an attractive material for the potential applications in the fields of photocatalysts [1,3], solar energy conversion [2], gas sensing [4,5], adsorbents [6], lubricants [7], lithium ion batteries [8], magnetic memories [9] and so on. Different morphologies of Cu 2 O crystals have their own advantages.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been extensively used in attempts to create trapped high-density excitons. Figures 7(a) and (b) illustrate the potential well formed in a Lucite crystal under Hertzian contact stress and a schematic of 7 One needs more than 10 T to observe noticeable exciton-level splitting in Cu 2 O induced by external magnetic field [Fishman et al (2009) stress experiments at low temperatures, respectively. Exciton drift into such a potential well in Cu 2 O at 2 K is clearly shown in Fig.…”
Section: Efficient Quadrupole Polariton Generation With Unconventionamentioning
confidence: 99%